Development of bread technology with high biological value and increased shelf life - Samilyk, Maryna; Demidova, Evgenia; Bolgova, Natalia; Savenko, Oleh; Cherniavska, Tetiana (Eastern-European Journal of Enterprise Technologies, 2022)
As an additive to bread, it is proposed to use a powder made from derivatives of Sorbus aucuparia mountain ash processing. The powder production technology involves freezing fruits, preliminary dehydration by osmotic dehydration, drying in an infrared dryer and grinding. The technology of bread with an extended shelf life and increased biological value has been developed, and some of its physical and chemical properties have been studied. To determine the feasibility of using powders from Sorbus aucuparia processing derivatives, their amino acid spectrum was analyzed by the chromatographic method. 17 amino acids in the amount of 7.43 g/100 g were identified, 7 of which are essential (valine, leucine, isoleucine, lysine, methionine, threonine, phenylalanine) in the amount of 1.84 g/100 g. The highest concentration of the total number of amino acids is glutamic acid (1.57 g/100 g), which gives the powders the properties of natural preservatives, increases the storage capacity of bread. The experiment showed that adding 20 % powder from Sorbus aucuparia processing derivatives to wheat flour bread allows at least doubling its shelf life. However, such an amount of additive affects the porosity of the bread and its organoleptic properties. Therefore, a sample was made with the addition of 10 % powder, and no defects in taste, smell and shape of bread with the addition of mountain ash powder were found. When using the developed technology, the time for making bread is reduced by 30 minutes compared to the classic straight dough method and by 120–150 minutes compared to the sponge dough method. The shelf life of bread according to the proposed technology is 15 days